Pengaruh Pemberian Jus Jambu Biji Merah terhadap Peningkatan Kadar Hemoglobin pada Ibu Hamil Trimester III di PMB Debby, Deli Serdang Tahun 2022 - Debby Rahmasari; Ester Simanullang; Nur Aisyah (Jurnal Siti Rufaidah, 2024)
One of the indicators based on the Sustainable Development Goals (SDGs 2030) is to support welfare and ensure a healthy life for all at all ages with the most important point being to reduce maternal mortality to less than 70 per 100,000 live births and prevent neonatal and toddler mortality rates of at least 12 per 1000 live births and 25 per 1000 live births in toddlers. A study was conducted to determine the effect of giving red guava juice on changes in hemoglobin levels in pregnant women in the third trimester at PMB Debby Deliserdang in 2022. In this study, the sample used was all pregnant women in the third trimester in March to May 2022, totaling 12 people. The study showed that in the intervention group before giving red guava juice, the majority had moderate anemia with a frequency of 8 respondents (66.7%) and a minority were normal with a frequency of 1 respondent (8.3%). Meanwhile, after giving red guava juice, the majority were normal with a frequency of 7 respondents (53.8%) and a minority of moderate anemia as much as 1 respondent (8.3%). The results of the analysis test in this study using Mann Whithney showed a P-Value of 0.022 (P <0.05), namely that there is an effect of giving red guava juice on increasing hemoglobin in pregnant women in the second trimester. Pregnant women, especially pregnant women who experience anemia, are expected to routinely consume red guava juice because if consumed properly, red guava juice has many benefits, especially for pregnant women so that it can meet the nutritional needs required by the body and can maximize iron absorption.